(untitled) (Eurasian Journal of Philology Science and Education, 2016)
This article provides the rationale for making strategic changes in the content of the scientific report. It is proposed to establish in the discourse of the scientific report just two formations of strategic preferences: on the one hand, the description of the scientific results as a product of the conceptualization of scientific experience, and on the other, – the alignment of marketing strategy as a tool for its commercialization. The article demonstrated the basic tool of scientific conceptualization of experience in describing the results of the study – a system of verbal concepts event type. Semantic verbal volume concept allows us to describe the content of the events, that represent in the minds of the propositional structure of the script. The results of the semantic analysis of the texts of reports showed that of the four types of scenarios used in the text of the report, only one describes the actual results of the study. In this description, the extrapolation of the results of research of the accounting documentation related to marketing communications becomes very difficult.